Development of the piezovane for estimating liquefaction potential of saturated sands - Butler, Leo Wm., author; Charlie, Wayne A., advisor; Siller, Thomas J., committee member; Doehring, Donald O., committee member (Colorado State University. Libraries, 1994)
The Piezovane was developed for determining in situ liquefaction potential of saturated sands by measuring the porewater pressure response oi saturated sand during and after shearing of the soil. A negative porewater pressure response is an indication that the material is in a dense (dilative) state; therefore is not susceptible to liquefaction failure. Positive porewater pressure response is an indication that the sand is in a loose (contractive) state and is susceptible to liquefaction-type failure. This project included design, fabrication of the Piezovane apparatus and the calibration chamber for the initial laboratory testing. Sands were placed within the calibration chamber at densities greater than or less than densities at the steady state which had been developed by using CU triaxial and CD direct shear tests. Trends indicate that the Piezovane testing can predict contractive or dilative behavior of soils. Additional testing both in the laboratory and in the field is required to determine whether these measured porewater pressure responses and measured shear resistances provide parameters needed for evaluating liquefaction potential and their possible use for design. A patent for the Piezovane has been awarded.
Covers not scanned.
Keywords: Soil liquefaction; Soil mechanics